2016
DOI: 10.1111/ppa.12494
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Penicillium species in the pear supply chain

Abstract: Postharvest fruit decay caused by Penicillium pathogens is considered to be one of the most important challenges in the pear industry resulting in market-end losses. Moving export fruit through different environments exposes the product to extensive handling, temperature variations and microbes. Therefore, the profile of Penicillium spp. present in the pear export chain from South Africa (SA) to the UK was studied over a four-year period. Sampling was done at two packhouse facilities, controlled atmosphere and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Penicillium polonicum was the second most dominant Penicillium specie found in this study. This specie was isolated by (Scholtz and Korsten 2016) from the pear export chain. Also, P. polonicum is common to cause decay in postharvest environment on stored onions (Duduk et al 2014), stored yam (Kim et al 2008) and stored cactus pear (Faedda et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Penicillium polonicum was the second most dominant Penicillium specie found in this study. This specie was isolated by (Scholtz and Korsten 2016) from the pear export chain. Also, P. polonicum is common to cause decay in postharvest environment on stored onions (Duduk et al 2014), stored yam (Kim et al 2008) and stored cactus pear (Faedda et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The third identified species, P. glabrum, can cause decay on wide range of produce (Pitt & Hocking, ). The 4‐year investigation of Scholtz and Korsten () showed that P. glabrum was the most dominant Penicillium species in the pear supply chain. Having in mind its wide host range, it could mean that the presence of P. glabrum and a susceptible host such as onion bulbs may lead to future blue mould decay and postharvest losses if packing and storage environments continue to share different commodities.…”
Section: Discussionmentioning
confidence: 99%
“…These species have a worldwide distribution, diverse range of habitats, and some are postharvest pathogens of food crops (Frisvad & Samson, ; Pitt & Hocking, ). Penicillium species produce a high number of airborne conidia which contaminate floors, walls, wooden bins, equipment and atmospheres in storage facilities and have been isolated from these environments in fresh produce supply chains (Amiri & Bompeix, ; Scholtz & Korsten, ). Blue mould is one of the primary diseases responsible for crop losses of bulbs and vegetables during storage and on onion bulbs it is mainly caused by Penicillium species from the series Corymbifera (section Fasciculata ) (Dugan, Lupien, Vahling‐Armstrong, Chastagner, & Schroeder, ; Overy, Frisvad, Steinmeier, & Thrane, ).…”
Section: Introductionmentioning
confidence: 99%
“…Methods used for quantification, isolation, grouping and identification of isolated Penicillium spp. were described in Scholtz & Korsten (Scholtz and Korsten, 2016). Penicillium colonies were counted and isolates were grouped according to similar cultural characteristics such as: colony size, color, texture and formation; mycelia coloration and formation; reverse plate coloration and the production of exudates.…”
Section: Identification Of Penicillium Species and Data Analysismentioning
confidence: 99%